Analisis pengaruh faktor cuaca terhadap dinamika populasi wereng batang coklat (Nilaparvata lugens Stål) yang tertangkap lampu perangkap - Sofyan, Devied Apriyanto; Koesmaryono, Yonny; Hidayati, Rini (Perhimpunan Entomologi Indonesia, 2019)
Nilaparvata lugens Stí¥l (brown planthopper [BPH]) is one of the major pests that cause a decline in rice productions. BPH population abundance in rice crops is affected by weather factors. An early indication of the BPH population abundance in the crop can be seen from the number of captured BPH on light traps. This study aims to analyze the influence of weather factors on the population dynamics of BPH, caught by the light traps. The method analysis used is correlation analysis and linear regression analysis. When multicollinearity problems occur among the weather factors, the influence was analyzed using principal component regression method. The result showed that rainfall, minimum humidity, and rainy days have a strong correlation to the BPH population dynamics. Based on subset tests between these three factors, two best factors were chosen, namely the rainy days and minimum humidity. The regression equation between rainy days and minimum humidity against the BPH population clearly describes the relationship of BPH population that increases along with the increase in the number of rainy days accompanied by the fluctuation of minimum humidity in the environment.